PENGARUH DOSIS KOMPOS PELEPAH KELAPA SAWIT TERHADAP HASIL UMBI PADA LIMA GENOTIPE UBI KAYU (Manihot esculenta Crantz.) - Indah Mulyasari; Herman Herman; Dewi Indriyani Roslim (DINAMIKA PERTANIAN, 2015)
In order to get the optimum yield, fertilization should be based on plant need of nutrient. The aim of this research was to find out the optimum dosage of oil palm stem compost for tuber yield of five cassava genotypes. The research was conducted at the biology experimental farm of Riau University, Pekanbaru situated at above ± 5 meters elevation during eleven months from July 2013 to May 2014. The research was arranged in the Randomized Block Design with two factors. The first factor was five cassava genotypes namely: Emas cassava (IM1), Lambau cassava (IM2), Menggalo cassava (IM3), Pulut cassava (IM4), Grafting cassava (IM5). The second factor was dosage of oil palm stem compost with three levels namely: 0 kg (P0), 5 kg (P5), 7 kg (P7). The parameters observed were plant height, number of tubers/plant, tuber diameter, tuber length, and tuber weight/plant. The results showed that there was significantly interaction between doses of oil palm stem compost and cassava genotypes on the tuber weight/plant but not significantly on plant height, number of tubers/plant, length and diameter of tuber. The compost with dosage of 5 kg was optimum for Lambau and Pulut cassavas, while the compost with dosage of 7 kg was optimum for Emas, Menggalo, and Grafting cassavas.